Istota i rozwój analizy przyczynowo-skutkowej z wykorzystaniem wskaźników - Borys, Tadeusz (The concept and development of the cause-effect analysis including the implementation of indicators, 2006)
The indicator type of analysis in a cause-effect system is, in fact, the development of a complex theory of a given phenomenon (e.g. poverty, climate changes etc.) with a logically ordered sequence of mutually interconnected indicator-oriented information, easy to translate into a sequence of objectives and strategic activities and - to a large extent - explaining the mechanism of how the occurrence of interest takes place. The scope of work that still has to to be performer is shown by the indicator type of gaps (“blank spaces”) in the OECD or UN systems of indicators. They refer mainly to pressure/cause indicators and response indicators. The significant importance of this analysis – in spite of the significant accomplishments of the UN, OECD, the World Bank or the European Union agencies - is still, and not only in Poland, far underestimated.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 60-69